The Correlational Relationship between Residential Satisfaction, Place Attachment, and Intention to Move: A Preliminary Study in Belawan, Medan - Amelia Tri Widya; Hanson Endra Kusuma; Rizal Arifin Lubis (Journal of Regional and City Planning, 2019)
Intention to move is an attitude affected by dissatisfaction toward one's residence. However, there is no clear correlation between the mediating variable of residential satisfaction and intention to move. The bond or attachment towards a place is one of the factors that cause a person's attitude or behavior. Regarding such a case, this study aimed to find out the correlational relationship between the level of satisfaction and place attachment to the attitude of intention to move. By using a mixed-method approach, this study examined the assessment of physical and non-physical aspects of satisfaction and place attachment dimensions. The research was conducted in Medan Belawan District, Medan City in a slum area that is part of a suburb of Medan. Questionnaires were distributed both directly in the field and online. The collected data were analyzed by principal component analysis and multivariate correlation analysis to seek the relationship between latent variables. The results showed that functional and cognitive attachment are the main predictors of mismatch and opportunities elsewhere.Abstrak. Keinginan pindah merupakan sikap yang dipengaruhi oleh ketidakpuasan seseorang terhadap tempat tinggal. Namun, belum ada korelasi yang jelas antara variabel mediasi kepuasan bermukim dan keinginan pindah. Ikatan atau keterikatan terhadap suatu tempat berperan sebagai salah satu faktor yang mempengaruhi sikap atau perilaku seseorang. Sehubung dengan hal tersebut, penelitian ini bertujuan untuk mengetahui hubungan korelasional antara tingkat kepuasan dan keterikatan tempat dengan sikap keinginan untuk pindah. Dengan menggunakan pendekatan metode campuran, penelitian ini menguji penilaian aspek fisik dan non-fisik dari kepuasan bermukim dan dimensi keterikatan tempat. Penelitian ini dilakukan di Kecamatan Medan Belawan, Kota Medan yang merupakan daerah kumuh pinggiran kota. Kuesioner didistribusikan secara langsung di lapangan maupun online. Data yang dikumpulkan dianalisis dengan analisis komponen utama dan analisis korelasi multivariat untuk mencari hubungan antara variabel laten. Hasil penelitian menunjukkan bahwa keterikatan fungsional dan kognitif merupakan prediktor utama ketidakbetahan dan peluang pindah.Kata kunci. Keterikatan kognitif, keterikatan fungsional, keinginan untuk pindah, kepuasan bermukim.